Wykorzystanie badań marketingowych w zarządzaniu współczesnym przedsiębiorstwem - Proszowska, Anita (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
This article summarize the knowledge about marketing research. The author also presents results of own survey of the methods used by modern Polish companies to implement marketing research in their management. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 273-279